Plan de marketing para la farmacia central, de la ciudad de Nueva Loja, cantón Lago Agrio, provincia de Sucumbíos, para el año 2016 - Jaramillo Japón, Pablo Rodrigo (2017)
Central Pharmacy today has several shortcomings, among them the application of old strategies that do not help to obtain a greater profitability, such as discounts in minimum amounts, leaving aside the advertising, promotions, and training to the personnel that attend to the clients. Therefore, a general objective was set for the development of this thesis work, which is to Elaborate a Marketing Plan for the Central Pharmacy of Pacayacu Parish, Lago Agrio Canton. This objective was raised since the Pharmacy requires important changes, bearing in mind that it lacks new marketing tools, which allow it to give a better image and attract more customers. For this, methods such as deductive, inductive, descriptive and analytical were used. In addition, some specific objectives were set out. The first one was to carry out a situational diagnosis, where information was verified with respect to the four PSs. The second objective was to perform the internal and external analysis, where techniques such as interviewing the Pharmacy Manager, And the surveys of the 6 employees and a sample of 265 clients, the EFI Matrix was also elaborated, where a total of 2.41 was obtained, showing that the weaknesses are surpassing the strengths, later the matrix EFE with a total of 2.74, which means that the opportunities are on the threats. Within the external analysis, the third objective was to carry out a market analysis to determine the opportunities and threats, as well as the ease it presents in the market. Then, the objective was to carry out the High Impact matrix, where the strategies to be carried out were determined, followed by the specific objective five and six, which is the proposal of the plan with the respective development of the objectives, their activities, goals , Tactics and budgets. As a general conclusion, the development of five strategic objectives derived from the results of the FODA, which show the owner of the Central Pharmacy new marketing alternatives that will expand its market segment and obtain greater profits, the total budget that Should be invested is $ 20385,40, costs are high considering that it is proposed to open a branch of the pharmacy in the center of Lago Agrio